A novel process for nutrients removal and phosphorus recovery from domestic wastewater by combining BNR with induced crystallization - Zou, Haiming; Lu, Xiwu; Li, Ting (Journal of Environmental Engineering and Landscape Management, 2014)
An excessive discharge of phosphorus from wastewater to water bodies may potentially contribute to eutrophication. On the other hand, mineral phosphorus resources will be depleted in the near future, because of difficulty to automatically recycle from water to land, unlike nitrogen. A new process for nutrients removal coupled with phosphorus recovery was proposed in this study by combining biological nutrients removal (BNR) with induced crystallization (IC), BNR-IC for short later, differently from conventional phosphorus recovery process. Our results showed that the BNR-IC system can maintain not only high and stable carbon, nitrogen and phosphorus removal efficiencies, all presenting above 90%, but also good phosphorus recovery performance from synthetic domestic wastewater, displaying about 70.2% of phosphorus recovery rate. When the COD, TN, NH4–N and P concentrations of 250 mg L−1, 42 mg L−1, 40 mg L−1, and 10 mg L−1, respectively were given in the influent, a stable removal efficiencies of 92.5% COD, 78.6% TN, 85.9% NH4–N and 95.2% P were obtained for the BNR-IC process and correspondingly the COD, TN, NH4–N and P concentrations of 18.75 mg L−1, 8.99 mg L−1, 5.64 mg L−1, 0.42 mg L−1 were monitored in the effluent, meeting the Chinese National Class I (grade A) Sewage Discharge Standard. Analyses of SEM and EDS, moreover, also demonstrated that the surface of seed crystal (calcite used here) was completely covered by hydroxyl calcium phosphate (HAP) produced during the induced crystallization process to recover phosphorus. Although our study involved only a small-scale trial, the proposed BNR-IC process here may be a promising technology, and can potentially aid in improvement of the effluent quality from WWTP and in recycle of mineral phosphorus resources when applied to practice.